Turkiston tizmasining shimoli-g‘arbiy qismida uchraydigan Ferula samarkandica Korovin, 1947 o‘simligi bilan bog‘liq hasharotlar - Usanov, U.N; Xalimov, F.Z (Actual problems and prospects of the study of the fauna, 2024)
In the article, the species composition of the entomofauna of the Samarkand blanket (Ferula samarkandica Korovin) in the north-western part of the mountain range of Turkestan at different altitudes from 1483 to 2048 meters above sea level was analyzed. 40 species of insects belonging to 5 families have been identified.